PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN BATU BARA DI BURSA EFEK INDONESIA (BEI) PERIODE 2017-2018 - Rina, Eneng (Nusa Putra University, 2020)
This research is to examine the effect of financial performance on the share price of coal mining companies on the Indonesia Stock Exchange for the 2017-2018 period. The independent variable here is financial performance by the Return On Asset (ROA) and Dividend Payout Ratio (DPR) variables, while the dependent variable is the stock price. Sample screening using purposive sampling. Data analysis used multiple linear regression analysis using SPSS. The result is that the partial ala (t test) of ROA and DPR does not have a significant effect on stock prices. Meanwhile, the simultaneous style (f test) shows that ROA and DPR have an effect on stock prices.